Transparency and numeric rules in the budgeting process: Theory and evidence - Nicolás Amoroso (Banco de México, 2008)
In this paper I develop a simple dynamic agency model postulating that, among budgetary institutions, transparency of the budgeting process is the main driving force in explaining differences in fiscal outcomes and that budgetary numeric rules can be an active long-run constraint only if the budgeting process is transparent enough. The model does not only account for long-run differences where countries with better budgetary institutions will have more disciplined fiscal outcomes, but can rationalize situations where countries with relatively better budgetary institutions can have what would appear to be less disciplined fiscal outcomes in the short-run. Empirical tests corroborate some but not all of the model's predictions.
Keywords: H61; D70; E60; 330; Budgetary Institutions; Fiscal Outcomes; Transparency; Öffentlicher Haushalt; Neue politische Ökonomie; Theorie